2016
DOI: 10.1111/cch.12331
|View full text |Cite
|
Sign up to set email alerts
|

“I think they're all basically the same”: parents' perceptions of human papilloma virus (HPV) vaccine compared with other adolescent vaccines

Abstract: Background Human papillomavirus (HPV) vaccination is recommended for routine administration at ages 11–12 years. However, uptake is lower than for other vaccines that are also routinely recommended for adolescents (MCV4 and Tdap). Understanding parental perceptions of HPV vaccine compared to other vaccines may help to inform strategies to increase uptake. Methods Parents and caregivers (n=45) of adolescents ages 10–18 years from a low-income, ethnic minority population participated in a qualitative study. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 25 publications
4
17
0
2
Order By: Relevance
“…This strategy of avoiding independent recommendations is similar to that suggested for HPV and other adolescent vaccines. 23,24 Further, we found a higher proportion of visits where clinicians used a participatory initiation format and did not pursue resistant parents for influenza compared to other vaccines. A similar discrepancy in clinician initiation format was demonstrated recently with HPV compared to other adolescent vaccines.…”
Section: Discussionmentioning
confidence: 73%
“…This strategy of avoiding independent recommendations is similar to that suggested for HPV and other adolescent vaccines. 23,24 Further, we found a higher proportion of visits where clinicians used a participatory initiation format and did not pursue resistant parents for influenza compared to other vaccines. A similar discrepancy in clinician initiation format was demonstrated recently with HPV compared to other adolescent vaccines.…”
Section: Discussionmentioning
confidence: 73%
“…Clinicians perceive HPV vaccine as less important than Tdap and MCV4 vaccines, which may also be a contributing factor to missed opportunities and/or a lack of urgency in addressing HPV vaccination resulting in suboptimal vaccination rates [6,16]. Moreover, linking vaccine administration for multiple diseases together (e.g., HPV, MCV4 and Tdap vaccines) may help to increase HPV vaccination rates [17]. …”
Section: Discussionmentioning
confidence: 99%
“…34,35 In a study of 2025 parents of adolescent daughters, Ogilvie et al 36 found that the odds of initiating the HPV vaccine were 8.5 times higher (95% CI, 6.1-11.9) among parents with positive (vs negative) attitudes toward vaccines. In the general population, positive attitudes toward vaccines overall have been associated with increased HPV vaccine uptake.…”
Section: Discussionmentioning
confidence: 99%
“…In the general population, positive attitudes toward vaccines overall have been associated with increased HPV vaccine uptake. 34,35 In a study of 2025 parents of adolescent daughters, Ogilvie et al 36 found that the [1] to most positive attitude [5]). [1] to highest perceived severity [5]).…”
Section: Discussionmentioning
confidence: 99%